Linking Environment, Conflict and Security: Emerging Scenarios and Implications for Sustainability in Developing Countries - Sudan, Falendra K. (Economic Journal of Nepal, 2014)
During recent past, the relationships among environmental change, conflict and peace have received considerable attention. Environmental stress is emerging as a major threat to peace and security in the developing world. There is a direct correlation between environmental degradation and conflict. Environmental degradation can and does trigger, amplify or cause conflict and instability. There is also increasing problem of environmental refugees. Growing environmental pressures may also soon create insecu-rities and possible conflict in countries of China, India and Brazil. It is likely that force may be used in response to trans boundary pollution, or to enforce international environmental law. Conflict can be a constructive force calling for institutional change. Environmental degradation and resource scarcity put pressures on existing institutions. All possible efforts will be made to bolster and adapt institutions to manage conflict effectively. Reducing poverty, strengthening the state and civil society, and promoting human rights will do more to enhance security and ensure peace. Awareness of linkages among environment, conflict and peace may help development agencies provide assistance that supports other policy objectives. Environ-mental degradation and peace are critical components of a fragile situation but important bridge between the development and security communities. Both have an opportunity to promote economic well being, social stability and environmental sustainability by strengthening that bridge. With above backdrop, an attempt has been made to explore the linkages among environmental change, conflict and security and to suggest policy recommendations addressing some urgent contemporary environmental and security problems in the context of sustainability and development. The Economic Journal of Nepal, Vol. 34, No. 3, July-September 2011 (Issue N0. 135)